The Influence of Social Media Marketing, Brand Engagement, and Product Quality on Purchase Decisions Mediated by Purchase Intention (Case Study of Wardah Lipstick Products in Bandung City) - Ardhya Arifah Zahro; Veronika Santi Paramita (Transpublika Publisher, 2025)
Cosmetics are a very important need for women to maintain their beauty. Due to diverse consumer demand for cosmetics, manufacturers create various cosmetic variants. However, it is different with wardah lipsticks which have experienced a decrease in the sales index according to the top brand index. This research focuses on analyzing how social media marketing, brand engagement, and product quality impact the decision to purchase Wardah lipstick products in Bandung, with purchase intention playing a role as a mediator. The study employs a quantitative methodology and utilizes purposive sampling to gather data from 100 respondents, determined using the Lemeshauw formula. Respondents are Wardah lipstick users in the millennial and Gen Z age ranges. The analysis in this study uses multiple regression and path analysis. The findings reveal that social media marketing, brand engagement and product quality positively significantly affect purchase intention. Social media marketing positively and significantly affect purchasing decisions. Meanwhile, brand engagement and product quality have no effect on purchasing decisions. Purchase intention plays a role in mediating the influence of social media marketing, brand engagement, and product quality on purchase decisions. This study found that purchase intention greatly affects the purchase decision. This study emphasizes the important role of social media marketing, brand engagement, and product quality in consumer decision-making when buying products, especially in the competitive cosmetics market.